2018
DOI: 10.1016/j.chempr.2018.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-Mediated Electron Injection from Au Nanorods into MoS2: Traditional versus Photoexcitation Mechanism

Abstract: How can plasmon-initiated charge injection from metallic particles into semiconductors compete with energy losses and charge recombination if the particles possess virtually no energy gaps? We show that the injection mechanism depends on particle-semiconductor interaction chemistry and system morphology and that the traditional mechanism, involving the rapid decay of plasmons into free electrons and subsequent charge injection, competes successfully with charge recombination in Au nanorods on the MoS 2 surface. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
104
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(107 citation statements)
references
References 85 publications
3
104
0
Order By: Relevance
“…The methodology has been applied successfully to study photoexcitation dynamics in a broad range of systems, including TiO 2 , 30 , 31 and it interfaces with electron donors, 32 35 metal halide perovskites, 36 38 and so on. 39 42 …”
Section: Methodsmentioning
confidence: 99%
“…The methodology has been applied successfully to study photoexcitation dynamics in a broad range of systems, including TiO 2 , 30 , 31 and it interfaces with electron donors, 32 35 metal halide perovskites, 36 38 and so on. 39 42 …”
Section: Methodsmentioning
confidence: 99%
“…One effective approach is to construct a heterostructure of plasmonic metal and semiconductor, in which an interfacial electric field exists at the plasmon-semiconductor interface, facilitating the effective separation of the generated hot electrons and holes. It has been reported that plasmonic metals (gold and silver) have been combined with many semiconductor materials, including TiO2 [74], zinc oxide (ZnO) [75], CdS [76], molybdenum disulfide (MoS2) [77], silver halides (AgX) [78], and bismuth oxide halides (BiOX) (X = Cl, Br, I) [79]. The obtained heterostructures showed enhanced photocatalytic performances, due to the improved charge separation.…”
Section: Hot Hole-involved Photochemistry At Plasmonsemiconductor Intmentioning
confidence: 99%
“…[14,15] Since these values are below the optical bandgap of MoS 2 (1.8 eV for a monolayer), a clever tuning of the PR spectral position, by appropriately changing the metal nanostructure dimensions or aspect ratio, can also potentially lead to sub-bandgap photon harvesting. According to a theoretical study, [16] charge transfer at the Au/MoS 2 interface efficiently competes with the onset of nonradiative carrier thermalization in gold and occurs via a traditional incoherent two-step process (i.e., without interfacial charge-transfer character) involving PRs decay in free hot electrons and injection above the Schottky barrier on ≈100 fs Hybrid plasmonic-semiconductor assemblies are receiving considerable attention due to the possibility to achieve hot-carrier-based photodetection. In this context, 2D transition metal dichalcogenides (TMDs) coupled to metal nanostructures are very promising.…”
Section: Introductionmentioning
confidence: 99%